Acoustic emission properties of concrete on dynamic tensile test. (1st July 2016) - Xiangqian, Fan; Shaowei, Hu; Jun, Lu; Congjie, Wei
Highlights: Introducing AE technology into the research of uniaxial dynamic tension. The cyclic loads was applied in order to achieve different initial damages of concrete specimen. The concrete AE signal exhibits Kaiser effects under dynamic loading. Kaiser effect is determined mainly by the interior damage level of concrete specimens. Abstract: In order to real-time monitor the internal damage of concrete and discussbasic characteristics of acoustic emission (AE) of concrete prism specimens under dynamic uniaxial tension, as well as the dynamic performance and failure mechanism of concrete, effect of the dynamic performance on structure are studied thoroughly, based on the AE rise time, ringing counts, energy, duration and amplitude of 60 different initial static load and different initial damage concrete dynamic axial tensile AE characteristics tests divided into 10 groups. Results are as follows: With the increase of initial quasi-static load value, the increase rates of acoustic emission parameters for concrete under dynamic loads gradually decrease; The larger the initial quasi-static load value is, the more difficult to identify the load's stable stage according to the acoustic emission signal, and the more significant hysteresis effect of concrete damage is; Under dynamic loads, the acoustic emission signal for concrete prism specimens also accord with Kaiser effect; Kaiser effect is determined mainly by the interior damage level of concrete specimens, not by the magnitude of load; The more initial loading cycles, the higher the degree of damage of specimens is, and the less acoustic emission signals are produced within the dynamic loading stage.